Ego and other tails - Cooke, Darwyn; Grist, Paul; Conner, Amanda; Palmiotti, Jimmy (DC Comics, 2025)
From comics visionary Darwyn Cooke comes this collection of stories starring two of Gotham City's most infamous residents in BATMAN: EGO & OTHER TAILS DELUXE EDITION! This deluxe edition graphic novel brings together the pulse-pounding stories featuring Cooke's incredible interpretations of Batman and Catwoman